Determinants of left atrioventricular coupling index as a prognostic marker of cardiovascular events from the multi-ethnic atherosclerosis study (MESA). (4th February 2022) - Pezel, T; Ambale Venkatesh, B; De Vasconcellos, H; Kato, Y; Post, W; Wu, C; Heckbert, S; Bluemke, D; Logeart, D; Henry, P; Lima, J
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND: Recent studies have emphasized the incremental prognostic value of a novel left atrioventricular coupling index (LACI) and its 10-year annual change (ΔLACI) to predict cardiovascular events. However, no study has investigated the potential determinants of this index. PURPOSE: To identify the determinants of LACI and ΔLACI, measured by cardiovascular magnetic resonance (CMR), and to better understand the parameters governing this left atrioventricular coupling in the Multi-Ethnic Study of Atherosclerosis (MESA). METHODS: In the MESA, 2, 112 study participants, free of cardiovascular disease at baseline, had LACI assessed by CMR imaging at baseline (LACIBaseline, Exam 1, 2000–2002) and 10 years later (Exam 5, 2010–2012). The LACI was defined as the ratio of left atrium to left ventricular (LV) end-diastolic volumes. Multivariable linear regression analyses were performed, adjusting for traditional risk factors and LV structure, to identify independent determinants of LACIBaseline or ΔLACI. RESULTS: In the 2, 112 participants (mean age 58.8 ± 9.1 years and 46.6% male), after adjustment for all covariates, age was independently associated with both LACIBaseline (R2 = 0.10) and ΔLACI (R2 = 0.15, both p < 0.001). Although there was no difference in LACIBaseline between women and men (p = 0.19), ΔLACI was higher in women than in men (1.0 ± 1.1 vs. 0.8 ± 1.0 %/year, p < 0.001). African Americans had the highest LACIBaseline value (18.0 ± 7.7%) while Chinese Americans had the lowest (13.8 ± 6.4%, p < 0.001). Diabetes and a higher body mass index were independently associated with LACIBaseline (coefficients B: 1.75 and 0.24, respectively, both p < 0.001). LACIBaseline was independently associated with LV myocardial fibrosis markers (native T1: R2 = 0.11, p = 0.038; and extra-cellular volume [ECV]: R2 = 0.08, p = 0.035) and NT-proBNP levels (R2 = 0.10, p < 0.001) but was not associated with inflammation biomarkers. CONCLUSIONS: In a multi-ethnic population, age, sex, ethnicity, diabetes, and a higher body mass index were independent determinants of LACI. LACI was independently associated with LV myocardial fibrosis markers and NT-proBNP levels but not associated with inflammation biomarkers. ClinicalTrials.gov Identifier: NCT00005487